Did poor eyesight influence Goya's late works? Medicine and art history in search for an interpretation of Goya's late paintings. Issue 6 (15th April 2018) - Pérez‐Trullén, José M.; Ascaso, Francisco J.; Auría, María J.
Abstract: Purpose: The aim of this article is to 'determine' the scope of Goya's eyesight difficulties and assess the extent to which those difficulties might explain his style of painting in the last years of his life. Methods: We analyse the correspondence and late works of the Aragonese painter Francisco de Goya y Lucientes (1746–1828), who has been admired for his use of colour, his energetic loose brushstrokes, his disregard for details and his bold compositions, as well as for his different artistic styles throughout his life. Results: The evolution of Goya's style of painting in his later works seems to have been the consequence of an eyesight condition, probably age‐related cataracts at an advanced stage. The faded dark backgrounds, which become blurred with the silhouette of the person portrayed, could indicate a certain degree of eye strain. This can be traced in all these works, but is especially evident in the unfinished portrait of Pío de Molina (1827–1828), as well as in the portraits of Mariano Goya, the artist′s grandson (1827), and Jacques Galos (1826). Conclusion: It has been considered that the late and isolated Goya′s sight problems were a belated consequence of his severe illness of 1792. Nevertheless, in our opinion, this is a simplistic explanation and, given the painter's age, it is logical to presume that their cause could be age‐related lens opacities. This article argues that medicine may become a subsidiary science to art history, as it can provide empirical evidence of the way painters' illnesses may have a strong impact on their artworks.